PENENTUAN DEFISIENSI BESI ANEMIA PENYAKIT KRONIS MENGGUNAKAN PERAN INDEKS sTfR-F - Adang Muhammad; Osman Sianipar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2005)
Background: The highest prevalence of nutrition problem due to nutrition deﬁciency is iron deﬁciency. Chronic disease anemia often occurs coincide with iron deﬁciency and both show of low iron serum appearance. Difﬁculty occurs when iron deﬁciency determined in chronic disease anemia by routine parameters. Bone marrow stainning can indicate iron store, but it is invasive. Therefore it needs another more practical parameter that has higher diagnostic value. Objective: To know the more practical parameter that can determine iron deﬁciency in chronic disease anemia Discussion: Ferritin serum indicates iron store in the body, whereas transferin receptor indicates functional of iron uptake in the erythrocyte. Changes of ferritin level due to inﬂammation process are varies. Recent evidence shows different changes of transferin receptor between iron deﬁciency anemia and those in chronic disease anemia. In chronic disease anemia, receptor transferin level increase but not as high as in those who suffer from pure iron deﬁciency anemia. Studies on groups of iron deﬁciency anemia, iron deﬁciency with acute inﬂammation, chronic disease anemia and healthy control population showed signiﬁcance differences of receptor transferin among them. sTrF-R index is an index derived from the calculation of transferin receptor level divided by logarithmic of the ferritin level. The usage of sTfR-F index indicates more signiﬁcance difference as compared to transferin receptor. Its sensitivity and speciﬁcity increase when it is applied to diagnose iron deﬁciency in elderly group. Conclusions: sTfR-F index is more sensitive and specific for the determination of iron deficiency in chronic disease anemia